Exploration of cohesive devices of English to streamline Arabic communication skills - Muritala , Yahya Toyin (2013)
The aim of this paper is to highlight the cohesive tools discussed by the Scholars of English Language with the effort of putting them into use in the modern Arabic Language. The study which relies on the descriptive and analytical methods will answer some questions on the possibility of borrowing the linguistic ideas from one language to another in spite of different origins. Although, Arabic has some distinct features, as a Semitic Language, which are not available in most European Languages including English, it can still be benefited through the application of cohesive devices studied in English for the purpose of effective global communication. The paper also suggests instances in which such devices may be applied in Arabic. Furthermore, it concludes with references to the cohesive usages in the Arabic Classical Texts like Qur'an, prophetic traditions and in the literary works of the early Arab Scholars, as it also affirms that exploration and exploitation of the English cohesive devices should not be the factor for the annihilation of the principles of the standard Arabic when it comes to the real communication skills and analysis.